2011
DOI: 10.1111/j.2042-7158.2011.01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of cerebral infarction and improvement of neurological deficit by a Korean herbal medicine, modified Bo-Yang-Hwan-O-Tang

Abstract: Taken together, our data suggest that mBHT has multiple anti-ischaemic properties and would be a good therapeutic herbal prescription for the treatment of cerebral ischaemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Another version of mBHD with added Polygalae radix and Acori Graminei Rhizoma showed anti-inflammatory and antioxidant effects on microglial cells [20]. Two studies using modified BHD with Achyranthis Radix, Acori Graminei Rhizoma, Polygalae Radix, Cinnamomi Ramulus, and Salviae Miltiorrhizae Radix reported reduction of the cerebral infarction size and neurological deficit in ischemia/reperfusion models [14] and hippocampal inflammatory responses in vascular dementia models [15]. A BHD preparation including Lycopi Herba, Typae pollen, Trogopterori feces, and Corydalis tubers showed antithrombotic activities and can be applied to diverse female diseases caused by thrombosis and inflammation such as endometriosis, myoma, and chronic pelvic inflammatory disease [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another version of mBHD with added Polygalae radix and Acori Graminei Rhizoma showed anti-inflammatory and antioxidant effects on microglial cells [20]. Two studies using modified BHD with Achyranthis Radix, Acori Graminei Rhizoma, Polygalae Radix, Cinnamomi Ramulus, and Salviae Miltiorrhizae Radix reported reduction of the cerebral infarction size and neurological deficit in ischemia/reperfusion models [14] and hippocampal inflammatory responses in vascular dementia models [15]. A BHD preparation including Lycopi Herba, Typae pollen, Trogopterori feces, and Corydalis tubers showed antithrombotic activities and can be applied to diverse female diseases caused by thrombosis and inflammation such as endometriosis, myoma, and chronic pelvic inflammatory disease [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various versions of modified BHD (mBHD), a combination of BHD and other effective herbal components, have been used for a synergistic therapeutic effect. Previous studies have reported the effects of mBHD on sciatic nerve injury [11], focal cerebral ischemia [14], and vascular dementia [15].…”
Section: Introductionmentioning
confidence: 99%
“…For the neuroprotective mechanism, BYHWD has been demonstrated in vitro to promote growth and differentiation of neural cells (Sun et al, 2007), and to inhibit apoptosis of nerve cells (Li et al, 2003a,b have indicated that BYHWD reduces ischemia/reperfusion damage via inhibition of the thioredoxin system (Wang and Jiang, 2009), [Ca 2+ ] (Sun et al, 2007), apoptosis formation (Li et al, 2003a,b), and free radical scavenger activity (Choi et al, 2011), suggesting that neuroprotective effects of BYHWD on brain ischemia are through multiple mechanisms. One of the mechanisms of cerebral ischemia/reperfusion injury involves glutamate.…”
Section: Introductionmentioning
confidence: 97%
“…Modified Bo-yang-Hwan-O-Tang was composed of the 12 herbs described previously. [ 11 12 13 14 ] Each herb was purchased from Medicinal Materials Company (Kwangmyungdang Medicinal Herbs, Ulsan, Republic of Korea). All herbs were authenticated by Professor J-H. Lee, a medical botanist in the Department of Herbology, College of Korean Medicine, Dongguk University (DUCOM), Republic of Korea.…”
Section: Methodsmentioning
confidence: 99%
“…mBHT is comprised of twelve different herbs,[ 10 ] and previously reported its various effects such as vasodilation,[ 10 ] neuroprotection,[ 11 ] antioxidation,[ 12 ] antiinflammation,[ 13 ] and the amelioration of brain infarction, and edema and the neurological deficit by cerebral ischemia in rats. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%